Exploring Bark-Water Interaction Effects on Stemflow Nutrient Concentrations in Urban Trees - Lima, Marcelle Teodoro; Mathias, Samir Leite; Guandique, Manuel Enrique Gamero [UNESP]; de Menezes, Aparecido Junior; Van Stan, John Toland; Tonello, Kelly Cristina (Wiley, 2024)
This study investigates the influence of bark properties on nutrient fluxes in urban environments, focusing on the relationship between bark wettability, chemical composition, and the concentrations of nutrients in stemflow and adjacent soil across eight urban tree species. Through a comprehensive analysis involving chemical assays and ecohydrological measurements, we explored how variations in bark characteristics affect water interaction and subsequent chemical dynamics within urban landscapes. Contrary to the initial hypothesis that bark properties would significantly influence nutrient flux, results revealed a complex scenario where environmental and anthropogenic factors in urban settings seemingly overshadow the direct impact of bark characteristics on nutrient dynamics. Our findings indicate that while bark properties such as wettability and chemical composition do vary among tree species, these variations do not directly correlate with significant differences in stemflow or soil nutrient concentrations. This suggests a homogenising effect of urban environments on ecohydrological processes, highlighting the need for a broader understanding of urban forest ecology that incorporates both biological traits and urban-specific environmental influences. This research contributes to the field of urban ecohydrology by underscoring the complexity of nutrient fluxes in urban forests and suggesting that effective urban tree management requires an integrated approach that considers the interplay between tree physiological traits and urban environmental conditions. Our study calls for further research to unravel the intricate dynamics of urban ecosystems, aiming to enhance the sustainability and ecological benefits of urban forests.
Keywords: bark hygroscopicity; bark wettability; ecohydrology; ecosystems services; enrichment ratio; forest hydrology; urban ecology; urban hydrology